Quality Evaluation of Artemisia capillaris Thunb. Based on Qualitative Analysis of the HPLC Fingerprint and UFLC-Q-TOF-MS/MS Combined with Quantitative Analysis of Multicomponents - Ying Dai; Zhihua Dou; Rongrong Zhou; Lin Luo; Li Bian; Yufeng Chen; Jinhua Tao; Zhixian Chen (Journal of Analytical Methods in Chemistry)
In this study, a new method was developed for the comprehensive quality evaluation (QE) of Artemisia capillaris Thunb. (A. capillaris, named Yinchenhao in Chinese), which is one of the most commonly used herbal medicines (HMs). First, fingerprints of 31 batch samples of A. capillaris were determined by HPLC, the reference fingerprint was established, and the common peaks were assigned. Second, the components of common peaks in the HPLC fingerprints were identified by ultrafast liquid chromatography- (UFLC-) Q-TOF-MS/MS. Finally, the contents of the components unambiguously confirmed by reference substances were determined, and the correlation between the contents of chlorogenic acid and the contents of others was analyzed. The results showed that there were 20 common peaks in the HPLC fingerprints of 31 batch samples. The components of these 20 common peaks were identified as ten organic acids, eight flavonoids, and two others. Among nine organic acids such as 1-caffeoylquinic acid, neochlorogenic acid, chlorogenic acid, caffeic acid, cryptochlorogenic acid, 1,3-dicaffeoylquinic acid, 3,4-dicaffeoylquinic acid, 3,5-dicaffeoylquinic acid, and 4,5-dicaffeoylquinic acid, three flavonoids such as rutin, hyperoside, and isoquercetin, and one other p-hydroxyacetophenone, a total of 13 ones were unambiguously identified by comparison with reference substances; one caffeoylquinic acid glucoside and one flavone di-C-glucoside were detected in A. capillaris for the first time. There were some differences in the contents of 13 components in different samples; chlorogenic acid could be regarded as the quality marker of A. capillaris. The current established method in this study can be used for the comprehensive QE of A. capillaris and can also provide reference for the QE of the other HMs.